Periphytic Diatoms in the Polluted Linggi (sensu stricto) and Kundor Rivers, Negeri Sembilan, Malaysia - I.S.A. NATHER KHAN (ASEAN Journal on Science and Technology for Development, 2015)
The investigation in this paper aimed to describe periphytic diatom assemblage, species composition and distribution in tropical polluted Linggi (sensu stricto or s.s.) and Kundor rivers in  Negeri Sembilan, Malaysia.  Regardless of ecological and environmental conditions, diatoms were the numerically dominant flora among periphytic  algae  collected monthly over a period of 13 months at nine stations in the Linggi (s.s.) and Kundor rivers.  The freshwater periphytic diatom samples were collected mainly using artificial substrates and supplemented with natural substrates.  The periphytic diatoms thus collected from both natural and artificial substrates comprised 86 taxa (82 pennate and 4 centric forms) belonging to 21 genera. Of the 86 species, 71 species were found colonized in artificial substrates while the remaining 15 species were recorded exclusively on natural substrates. On the whole, the most common diatoms in both rivers combined were Eunotia vanheurckii, Gomphonema parvulum, Nitzschia palea, Pinnularia braunii, Navicula cryptocephala, Achnanthes saxonica, Achnanthes minutissima and Pinnularia microstauron.  The most abundant species were E. vanheurckii, N. palea, A. saxonica, G. parvulum and A. minutissima.